The Genome of a Thermo Tolerant, Pathogenic Albino Aspergillus fumigatus - Couger, Brian; Weirick, Tyler; Damásio, André R. L.; Segato, Fernando; Polizeli, Maria De Lourdes Teixeira De Moraes; de Almeida, Ricardo S. C.; Goldman, Gustavo H.; Prade, Rolf A. (Frontiers in Microbiology, 2018)
Biotechnologists are interested in thermo tolerant fungi to manufacture enzymes active and stable at high temperatures, because they provide improved catalytic efficiency, strengthen enzyme substrate interactions, accelerate substrate enzyme conversion rates, enhance mass transfer, lower substrate viscosity, lessen contamination risk and offer the potential for enzyme recycling. Members of the genus Aspergillus live a wide variety of lifestyles, some embrace GRAS status routinely employed in food processing while others such as Aspergillus fumigatus are human pathogens. A. fumigatus produces melanins, pyomelanin protects the fungus against reactive oxygen species and DHN melanin produced by the pksP gene cluster confers the gray-greenish color. pksP mutants are attenuated in virulence. Here we report on the genomic DNA sequence of a thermo tolerant albino Aspergillus isolated from rain forest composted floors. Unexpectedly, the nucleotide sequence was 95.7% identical to the reported by Aspergillus fumigatus Af293. Genome size and predicted gene models were also highly similar, however differences in DNA content and conservation were observed. The albino strain, classified as Aspergillus fumigatus var. niveus, had 160 gene models not present in A. fumigatus Af293 and A. fumigatus Af293 had 647 not found in the albino strain. Furthermore, the major pigment generating gene cluster pksP appeared to have undergone genomic rearrangements and a key tyrosinase present in many aspergilli was missing from the genome. Remarkably however, despite the lack of pigmentation A. fumigatus var. niveus killed neutropenic mice and survived macrophage engulfment at similar rates as A. fumigatus Af293.